If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + (-16) = 24 + 12 -2y + -16 = 24 + 12 Reorder the terms: -16 + -2y = 24 + 12 Combine like terms: 24 + 12 = 36 -16 + -2y = 36 Solving -16 + -2y = 36 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -2y = 36 + 16 Combine like terms: -16 + 16 = 0 0 + -2y = 36 + 16 -2y = 36 + 16 Combine like terms: 36 + 16 = 52 -2y = 52 Divide each side by '-2'. y = -26 Simplifying y = -26
| 3x-(12-x)=28 | | 29-x=x+5 | | 29-x =x+5 | | 5(x+1)=3x+12 | | 10-(x-5)=40 | | 3y+12=y+8 | | 1=1.25-a^2 | | N=0.04x-78.40 | | 2(4y+8)=3(2y-2) | | -7(t-9)-(t+6)=3 | | 8-y+2y=17 | | 7x-10.8=x | | t=3g+3uwhatisg | | t=3g+3u | | 12x-109=5x-11 | | 86-2x=16x+22 | | -11-9x=7x+22 | | 7+8x=7x-1 | | -6w-8=46 | | 15x^2-3x=3-7x | | -5x-3=-13 | | 5x^2-44x+120=-30+11x | | -5(2)-3=-13 | | X+.5=.25x-.62 | | X+.5=.25-.62 | | 24x^2+24x-18=(ax-3)(4x+a) | | 23x-y=42y+x | | 2(t+5)+t=4 | | -5-3=-13 | | y+x=1 | | 3[x-(2+3x)]=2x+2 | | t=5k+5z |